Al-Islām wa Qadhāyā Kurūnā: Dirāsah Muqāranah Bayna Al-Fatwā fī Mishr wa Indūnīsiyā - JM Muslimin; Mahmoud Mohamed Hosny Mohamed; Wildan Munawar (Universitas Islam Negeri Jakarta, 2021)
This article discusses how Indonesia and Egypt dealt with Covid-19 from the Islamic law perspective. It focuses on fatwas regarding the establishment of religious rites in the Covid-19 periode. The study compares the two experiences in terms of the Islamic jurisprudential methodology and the fatwa issuance procedural systems. It analyzes the Islamic legal comparison between the Indonesian and Egyptian experiences in dealing with the Covid-19. This study found that the fatwa regarding Covid-19 in Egypt is responsive to the virus's rapid transmission. Therefore, Muslims have guidelines in performing worship during the Covid-19 period. The sharia arguments used in formulating the fatwa for the implementation of worship during the Covid-19 period are qiyas, maṣlaḥat, sad al-dharā'i and the opinions of the jurists. This methodological argument is used in principle to avoid the danger of spreading Covid-19. Abstrak: Artikel ini membahas bagaimana Indonesia dan Mesir menghadapi Covid-19 dari perspektif hukum Islam. Fokus penelitian ini pada fatwa pelaksanaan ibadah pada masa Covid-19. Studi ini membandingkan dua segi metode yakni fikih Islam dan sistem prosedural penerbitan fatwa. Prosedur penelitian ini menganalisis perbandingan hukum Islam antara pelaksanaan ibadah di Indonesia dan Mesir pada masa pandemi. Studi ini menemukan bahwa fatwa tentang Covid-19 di Mesir tidak responsif sehingga penularan virus yang cepat, sedangkan fatwa umat Islam di Indonesia dapat dijadikan pedoman dalam menjalankan ibadah selama masa Covid-19. Dalil-dalil syariah yang digunakan untuk merumuskan fatwa pelaksanaan ibadah selama masa Covid-19 adalah qiyās, maṣlaḥat, sad al-dharā'i dan pendapat para fukaha. Adapun argumen metodologis ini pada prinsipnya digunakan untuk menghindari bahaya penyebaran Covid-19.